The Influence of Organizational Culture, Incentives and Motivation on Employee Performance of PT. Niaga Sejahtera Plastik Indonesia in Purwosari, Pasuruan Regency - Koen Irianto Uripan; Angga Martha Mahendra (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study aims to analyze the influence of Organizational Culture, Incentives and Motivation on Employee Performance of PT. Niaga Sejahtera Plastik Indonesia in Purwosari, Pasuruan Regency. The total sample of the study was 100 people. The variables used are organizational culture, incentives and motivation as independent variables and employee performance as the dependent variable. Data collection was carried out using a questionnaire and then analyzed using multiple linear regression analysis methods. Hypothesis testing used is the simultaneous significance test (F-test) and partial significance test (T-test). The results of the F test of this study indicate that the variables of organizational culture ( ), incentives ( ), and motivation ( ) have a simultaneous effect on employee performance. While the T test shows that the variable of organizational culture ( ), does not have a partial effect on employee performance, while the variables of incentives ( ), and motivation ( ) have a partial effect on employee performance.